Construct Validity and Reliability of Creativity and Innovation in Public Sector: A Rasch Measurement Model Approach for Pilot Study - Sapiyi, Saharah; Suradi, Nur Riza Mohd; Mustafa, Zainol (The journal of contemporary issues in business and government, 2021)
A pilot study is imperative to test the questionnaire items, confirm and check the research instrument’s reliability to obtain the best items. This pilot research aimed to test the reliability of the developed public sector instrument and identify its weakness. The instrument was purposefully designed to recognise the factors that affect creativity and innovation in the Malaysian public sector and their influence on government agencies’ performance. The instrument included 90 items and was distributed to 120 civil servants from several ministries mostly located in Putrajaya and Kuala Lumpur, Malaysia. The goal of this instrument was to measure five study constructs: individual creativity (IC), team creativity (TC), organisational innovation (OI), innovation processes (IP), and organisational performance (OP). The method employed to analyse the validity and reliability of the items and respondents in this study was derived from the Rasch Measurement Model Approach, which is far more valid and well-grounded than only relying on Cronbach’s Alpha output produced. The Winsteps version 3.73 was used to verify the items’ functionality in aspects such as the item’s reliability and separation of the item-respondent, polarity item, item fit in measuring constructs, item difficulty level, the respondent’s ability, and the standardised residual correlations. It also enabled the removal of items based on polarity items’ statistics and the item’s suitability. At the end of the analysis, it was established that there was a total of 9 items that were discarded because they did not meet the inspection criteria specified per the Rasch Model. A total of 81 items were recorded on the final instrument that could be used to measure the five constructs.